Junior High School Students Experiences On English-Indonesia Bilingualism: A Phenomenology Study - R. B. G, Sakul; B, Lumoindong (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The use of English-Indonesian languages has become a habit of students in the UNKLAB Adventist Junior High School environment. Bilingual language is a program that has long been implemented at UNKLAB Adventist Junior High School. Students inevitably have to adapt to the school environment to use both languages. This research aimed at determining junior high school students ' experiences of English-Indonesian bilingualism. The type of research used is qualitative research using a phenomenological approach to describe the reality that occurred. The data collection techniques used included observation, documentation and interviews to the 5 UNKLAB Junior High School students. The results of this research showed that the influence of bilingual language used by the junior high school students was caused by the influence of schools that organized the bilingual programs, teachers who helped and guided the students, and families where they grew. Suggestions of this research were the students needed to adapt to the school environment that has the bilingual program by improving themselves through a more serious learning program, the families have to involve more by guiding, training, and motivating the students at home to speak two languages, and teachers to pay more attention to the students who have not yet mastered the bilingual languages.